The US Anti-Dumping Measures in Law, in Practice and Their Problems - Lan Anh, Le (VNU Journal of Foreign Studies, 2021)
The US anti-dumping law is important in the US trade protection legislation in particular as well as the US trade law in general. The primary objective of US anti-dumping measures is to deal with dumping actions by foreign exporters in the US market to protect domestic producers. The objective of the paper is to analyze the current issues of the US anti-dumping measures in order to assess their feasibility. The research has shown that among the three US anti-dumping measures, price undertaking (suspension agreement) is a viable option for the parties to terminate anti-dumping investigation at its preliminary stage, but in fact, it is less applicable in practice; instead, anti-dumping duty is mostly used. This makes anti-dumping measures turn into a more likely tariff measure than a non-tariff measure.